Data network with layer protection of two models TCO/iP uti Using free software to improve link security The branches in the different entities or companies of Ecuador - Ing Carlos Cordón (2011)
Technology isdeveloping progressively in agreement totheexistences in thesociety and requíres a continuous acceptance totheir requirements, Every day appear new proposes to improve theservice ofthecompanies, for thisreason they areconsidered fundamental tochanges thattake place toimprove thelife ofhuman beings.Giving thebestservice totheclients isthefundamental objective ofthepublic companies, for this reason itis necessary todotheprocess ofwork with themost efficiency and with thebest elements. As a reference theselectedcompany is theillustrate town council ofPelileo (IMP) selected for my affinity because Ilive in thecity ofPelileo. Itisvery important tomention thatthe study has been done specifically in theTechnical University ofAmbato andthere is noí necessary confidential information ofthe Illustrate Town Council ofPelileo because Ioniy use the ñamefor reference. Publically express thatthere is not attempt against theIllustrateTown Council ofPelileo and Ilibérateofalltheresponsibilities ofmanaging information.Itis considered that the communication between branch offices ofthe public company is the fundamental element andfor reason is required tocontríbute tothecommunication has asecurity very effective thatisthefundamental objectivesX^^ofourinvestigation